A geomorphological approach to geodiversity – its applications to geoconservation and geotourism - Thomas, Michael (Quaestiones Geographicae, 2012)
Geodiversity is becoming widely considered alongside biodiversity by conservation agencies and has importance for geotourism. Geomorphology has a central role in understanding geodiversity, particularly at regional and local scales. By focusing on the processes that interact at the earth's surface and how they respond to external forcing, geomorphology analyses both landscape evolution and real-time changes over different timescales. Diversity reflects the complexity of process systems and history. Connectivity and sensitivity amongst landscape elements are highly varied over space and time, leading to divergence and increasing diversity over time. By using these principles within constrained chronologies of landscape change, studies of geodiversity can become a valuable tool in ecosystem management and the delivery of ecosystem services, including sustainable geotourism.